2017
DOI: 10.1016/j.ijcha.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac rehabilitation in patients with cardiovascular disease leads various hemodynamic parameters obtained using simple non-invasive tests to their appropriate levels

Abstract: We evaluated whether comprehensive cardiac rehabilitation (CR) in patients with cardiovascular disease (CVD) could improve various hemodynamic parameters obtained using simple non-invasive tests. We analyzed 48 CVD patients with (n = 38, CR group) or without (n = 10, non-CR group) a CR program, and prospectively followed them for 12 months. Various parameters were measured at baseline and after 12 months using 3 simple non-invasive tests: blood pressure (BP) and severity of atherosclerosis [arterial velocity p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…A relationship between low exercise capacity and the absence of SV increase during the nal phase of the exercise test, as well as between low exercise capacity and low absolute SV values at peak exercise, have been reported in nonathletic adults [21] and in patients with hypertension [12], diastolic left ventricular dysfunction [22] and HF [11,20]. Moreover, a number of authors have emphasized the association between regular physical exercise and SV improvement [23,24,25].…”
Section: Discussionmentioning
confidence: 92%
“…A relationship between low exercise capacity and the absence of SV increase during the nal phase of the exercise test, as well as between low exercise capacity and low absolute SV values at peak exercise, have been reported in nonathletic adults [21] and in patients with hypertension [12], diastolic left ventricular dysfunction [22] and HF [11,20]. Moreover, a number of authors have emphasized the association between regular physical exercise and SV improvement [23,24,25].…”
Section: Discussionmentioning
confidence: 92%
“…A relationship between low exercise capacity and the absence of SV increase during the final phase of the exercise test, as well as between low exercise capacity and low absolute SV values at peak exercise, have been reported in nonathletic adults [ 23 ] and in patients with hypertension [ 13 ], diastolic left ventricular dysfunction [ 24 ] and HF [ 12 , 21 ]. Moreover, a number of authors have emphasized the association between regular physical exercise and SV improvement [ 25 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have studied CR for more than eight years and reported some beneficial effects in patients with cardiovascular diseases (CVD) [12][13][14][15][16][17]. We previously reported that a CR program significantly reduced blood pressure (BP) and visit-to-visit variability in BP, and patients with mild to moderate chronic kidney disease (CKD) who participated in our CR program showed an increase in their estimated glomerular filtration rate (eGFR) [14,15].…”
Section: Introductionmentioning
confidence: 99%